Advancing Sustainable Development Goals: The Impact of Corporate Governance Mechanisms and Industry Type on Business Contributions - Elin Erlina Sasanti; Muhsyaf, Saipul Arni; Sapto Hendri BS (Riset Akuntansi dan Keuangan Indonesia, 2023)
The 2030 Agenda for Sustainable Development calls for global businesses to support Sustainable Development Goals (SDGs). This study examines the impact of corporate governance mechanisms, particularly board of directors' roles, on SDG achievement through company disclosures and explores industry type as a moderating factor. Analyzing 408 IDX-listed companies from 2018-2020, the study finds that CEO independence, independent boards of commissioners, and frequent board meetings can enhance SDG achievement as reported in financial statements. However, industry types may affect SDG achievement, potentially reducing the influence of CEO independence and independent boards of commissioners. The research highlights the significance of corporate governance mechanisms and industry type in promoting SDG achievement in businesses